Pengaruh Leverage dan Likuiditas terhadap Financial Distress dengan Sudut Pandang Profitabilitas sebagai Moderasi - Rangga, Tegar Dwi; Hapsari, Ira; Santoso, Suryo Budi; Santoso, Slamet Eko Budi (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to investigate the role of leverage and liquidity in financial distress, with profitability as a moderating variable in property and real estate companies listed on the Indonesia Stock Exchange (Bursa Efek Indonesia – BEI) during the 2021–2023 period. The research sample was selected using the purposive sampling technique, with criteria requiring companies to publish complete annual financial reports within this period. Based on these criteria, 68 companies were obtained as the research sample. Data analysis was conducted using SPSS 26 with the moderated regression analysis technique. The results indicate that leverage has a negative effect on financial distress, while liquidity has a positive effect on financial distress. However, profitability does not moderate the effect of leverage and liquidity on financial distress. These findings are expected to provide valuable insights for stakeholders in the property and real estate industry in designing strategies and making appropriate decisions to mitigate the risk of financial distress in companies.